2014
DOI: 10.1371/journal.pone.0111580
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Increases Impulsivity and Decreases Willingness to Exert Cognitive Effort despite Improving Attention in “Slacker” Rats: Insights into Cholinergic Regulation of Cost/Benefit Decision Making

Abstract: Successful decision making in our daily lives requires weighing an option’s costs against its associated benefits. The neuromodulator acetylcholine underlies both the etiology and treatment of a number of illnesses in which decision making is perturbed, including Alzheimer’s disease, attention-deficit/hyperactivity disorder, and schizophrenia. Nicotine acts on the cholinergic system and has been touted as a cognitive enhancer by both smokers and some researchers for its attention-boosting effects; however, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
3
17
1
Order By: Relevance
“…We opted to use female rats in the current study, given that they display similar patterns of behaviour on the rCET to the more commonly used males. Indeed, choice of the HR lever in this study was 66%, while HR choice has ranged from 56% (Hosking, Cocker et al, 2014) to 73% (Hosking, Lam et al, 2014) across male cohorts (HR choice is typically ~70%). Accuracy and premature responding rates are also similar to those typically observed in male cohorts.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We opted to use female rats in the current study, given that they display similar patterns of behaviour on the rCET to the more commonly used males. Indeed, choice of the HR lever in this study was 66%, while HR choice has ranged from 56% (Hosking, Cocker et al, 2014) to 73% (Hosking, Lam et al, 2014) across male cohorts (HR choice is typically ~70%). Accuracy and premature responding rates are also similar to those typically observed in male cohorts.…”
Section: Discussionmentioning
confidence: 82%
“…As such, improving the application or evaluation of cognitive effort may require us to look beyond the usual monoaminergic suspects typically associated with reward-related learning. Instead, cannabinoid and cholinergic receptor signalling appears to modulate rats’ willingness to put in attentional effort for more lucrative outcomes (Hosking, Lam et al, 2014; Silveira et al, 2016). Future work studying these pathways may be fruitful in identifying compounds capable of relieving anhedonia and other cognitive motivational deficits.…”
Section: Discussionmentioning
confidence: 99%
“…The RVP and IED were selected as pre-tests since both tests were successfully used to detect behavioural changes following cholinergic manipulations, such as the administration of nicotine or cigarette smoking (Sahakian et al, 1989;Jones et al, 1992;Nesic et al, 2011). In addition, previous results also support a link between impulsiveness and nicotine effects (Hosking et al, 2014). ADHD patients with high impulsivity tend to show larger nicotine effects on response inhibition (Potter and Newhouse, 2004;Potter et al, 2012) and previous fMRI studies revealed the largest effects of nicotine on the BOLD signal during inhibitory control in individuals with high levels of impulsivity (Kasparbauer et al, 2019).…”
Section: Behavioural Pre-tests For Assessment Of Baseline Cognitive Pmentioning
confidence: 99%
“…The NBM has strong projections to the prefrontal cortex (PFC), which enhances attention through acetylcholine binding to nicotinic receptors ( 6 ). When examining performance of this pathway in stressed rats, the authors found decreased acetylcholine output in stressed males only, matching their impaired attention.…”
mentioning
confidence: 99%
“…Acetylcholine binds to both nicotinic and muscarinic receptors in the PFC. Activation of nicotinic receptors improves attention while activation of muscarinic receptors increases impulsive behaviors ( 6 ). Eck et al.…”
mentioning
confidence: 99%